The rhetorical work of remediation in The Photographer. Issue 2 (1st October 2014) - Lawson, Daniel
For scholars in visual rhetoric, the recent wave of visual narrative forms have posed a particular challenge in terms of analysis: how might one read the sort of text that refuses to conform to visual genres as we have come to know them and yet draws upon a number of conventions from these genres and the media they typically appear in? As visual narrative forms like comics and their remediations become more ubiquitous, how do we read them and explicate what these forms have to offer in terms of meaning-making? One particularly compelling example can be found in The Photographer: Into War-Torn Afghanistan with Doctors Without Borders. This work incorporates a blend of media – such as prose, comics, and most especially photography – while eluding any easy designation into any one of those categories. Part travelogue and part photojournalism, The Photographer tells the story of Didier Lefevre's travels with Doctors Without Borders in Afghanistan during the war between the Soviet Union and the Afghan Mujahideen. Drawing upon scholars such as Barthes, Mitchell, Bolter and Grusin, as well as assorted comics scholars and commentators, I contend in this article that by positioning text against drawing and each against photography, The Photographer calls attention to the potential hegemonic function of any one of these discursive modes. Using close reading and rhetorical analysis, I explicate how the notion of hybridity informs the rhetorical work of the book in terms of its authorial voice(s), its form, and its content. By destabilizing fixed categories of medial and cultural identity, The Photographer enables its subjects to take on a sort of humanity than might otherwise be available to them in more traditional modes of representation and enables different forms of immediacy for its readers.